Additive Prognostic Value of Carotid Plaque Score to Enhance the Age, Creatinine, and Ejection Fraction Score in Patients with Acute Coronary Syndrome - Hayashi, Kenshi; Kawashiri, Masa-aki; Mori, Mika; Yamagishi, Masakazu; Takamura, Masayuki; Sakata, Kenji; Nomura, Akihiro; Tada, Hayato; Ohira, Miho; Nakahashi, Takuya (Journal of Atherosclerosis and Thrombosis, 2018)
Aim: To assess whether combining measurements obtained from carotid ultrasonography in addition to the age, creatinine, and ejection fraction (ACEF) score would improve the predictive ability of outcome in patients with acute coronary syndrome (ACS).Methods: We examined 264 patients with ACS (194 men; mean age: 68±11 years) who underwent percutaneous coronary intervention. The carotid plaque score (cPS) and intima–media thickness (cIMT) were determined by carotid ultrasonography. The modified ACEF score was calculated using the following formula: (age/left ventricular ejection fraction) ＋1 point for every 10 mL/min reduction in creatinine clearance below 60 mL/min per 1.73 m2. The endpoint of this study was major adverse cardiovascular and cerebrovascular events (MACEs), defined as all-cause death, myocardial infarction, stoke, and target vessel revascularization.Results: During the median 4-year follow-up, there were 121 incidents of MACEs. Multivariate Cox proportional hazard regression analysis revealed that cPS ≥9.8 (hazard ratio [HR], 1.52; 95% confidence interval [CI], 1.01–2.31) and ACEF score ≥1.20 (HR, 1.62; 95% CI, 1.11–2.39) were significantly associated with MACEs, whereas cIMT was not. When the new combined risk score was calculated by multiplying the cPS by the modified ACEF score, the freedom from MACEs at 5 years was 71% and 31% for the lower and higher scores, respectively (p＜0.001). The area under the receiver-operating characteristic curve for MACEs for the ACEF score, cPS, and combined risk score were 0.65, 0.66, and 0.71, respectively (p＜0.05).Conclusion: The cPS offers an incremental predictive value when combined to the simple ACEF score in ACS.